Sound Absorption of Natural Fiber Composite from Sugarcane Bagasse and Coffee Silver Skin - Wachara KALASEE; Putipong LAKACHAIWORAKUN; Visit EAKVANICH; Panya DANGWILAILUX (My University, 2023)
This study aimed to develop a sound-absorbing composite using sugarcane bagasse (SB) and coffee silver skin (CS) as raw materials. The composite boards were manufactured by bonding the fibers with Melamine Urea-Formaldehyde adhesive, ensuring a consistent thickness of 30 mm. Various densities were employed, namely 380, 450, and 520 kg/m3. The samples were fabricated with different fiber ratios, including SB100%, SB75% with CS25%, and SB50% with CS50%. The sound absorption coefficient (SAC) and noise reduction coefficient (NRC) were measured using the impedance tube method within a frequency range of 63–6,300 Hz. The experimental results revealed that the mixing ratio of CS exerted a notable influence on enhancing the SAC, while the density of the composite board exhibited a significant impact on increasing both the SAC and NRC. Among the densities tested, the optimal value was observed at 520 kg/m3, yielding a SAC value of 0.65 at a frequency of 1,000 Hz and an NRC value of 0.55 for the SB50-CS50 composite plate. These findings underscore the importance of considering the CS mixing ratio and composite board density when aiming to optimize sound absorption properties.
Keywords: Bagasse; Noise reduction coefficient; Urea-formaldehyde; Acoustic Wave Phenomena Research